Thermoeconomic Optimization and Performance Analysis of a Regenerative Closed Brayton Cycle with Internal Irreversibilities and Pressure Losses - Durmusoglu, Yalcin; Ust, Yasin; Kayadelen, Hasan Kayhan (SPRINGER, 2017)
Global demand for electricity is growing every year. Gas turbines are indicated to be one of the cleanest options running on fossil fuels to meet this growing demand. Apart from utility power generation, they are dominating the aviation industry and also being used in maritime industry as prime movers because of their characteristic advantages such as high power/weight ratio, wide operational flexibility, ease of maintenance and high reliability. Forecasts show that gas turbines will dominate the US power production industry in the near future. With growing interest on gas turbines, modifications on simple Brayton cycle are becoming more of an issue. Regeneration is one of these modifications which increases thermal efficiency for the same power output and provides less fuel consumption. Accordingly, employing a regenerator decreases fuel and environmental costs. In this paper, thermoeconomic performance optimization of a closed irreversible regenerative Brayton cycle has been carried out. A precise combustion tool based on chemical equilibrium approach has been used for the specification of adiabatic flame temperature which substantially affects environmental costs. For the optimization, the objective function is defined as the net power output divided by the total cost rate which includes the investment cost, fuel cost and environmental cost flow rates. Effects of isentropic and maximum temperature ratios, compressor and turbine isentropic efficiencies, regenerator effectiveness and pressure loss parameter on the thermoeconomic performance of the regenerative Brayton heat engine are investigated. Optimum values for power output, thermal efficiency, investment, fuel and environmental cost rates are specified and discussed.
Keywords: Thermoeconomic optimization; Regenerator; Brayton cycle; Environmental costs; RECUPERATED GAS-TURBINE; MULTI-CRITERION OPTIMIZATION; MULTIOBJECTIVE OPTIMIZATION; THERMAL EFFICIENCY; COGENERATION APPLICATIONS; HEAT ENGINE; POWER; REHEAT; ENVIRONMENT; OBJECTIVES; Engineering